2015
DOI: 10.1111/iej.12572
|View full text |Cite
|
Sign up to set email alerts
|

Apically extruded debris during root canal preparation using Vortex Blue, K3XF, ProTaper Next and Reciproc instruments

Abstract: All instruments were associated with apical extrusion of debris. VB and PTN files were associated with less debris extrusion compared to the other systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
3
29
4
1
Order By: Relevance
“…, Topcuoglu et al . ). Recent studies have reported effective debris and smear removal with minimal or no thermal damage to the organic dentinal structure through a photoacoustic technique called photon‐induced photoacoustic streaming or PIPS (DiVito et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Topcuoglu et al . ). Recent studies have reported effective debris and smear removal with minimal or no thermal damage to the organic dentinal structure through a photoacoustic technique called photon‐induced photoacoustic streaming or PIPS (DiVito et al .…”
Section: Discussionmentioning
confidence: 97%
“…It is also worth emphasizing that the results of the present study differed from those presented by Topçuoglu et al., in which the instrument of the reciprocating system (RC) promoted a higher apical debris extrusion value than those of the PTN system instruments . However, in the previously‐cited research, instruments of smaller diameter were used, demonstrating that instrument diameters could be a preponderant factor with respect to debris extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, experimental groups in comparative studies have been created by selecting randomized either single‐ or multi‐rooted teeth with limited sample size (Topçuoğlu et al 2016, Silva et al 2017, Pedullà et al 2019). In practice, this means a very poor standardization and the inability to ensure experimental comparability as it may yield experimental groups with large variations in the baseline of the substrate (Smith & Steiman 1994, També et al 2014).…”
Section: Introductionmentioning
confidence: 99%